Food Price, Oil Price and Exchange Rate Dynamics in BRICS: Panel VAR and Dynamic Panel Threshold Analyses - Sanusi, Kazeem Abimbola; Dickason, Zandri (Acta Universitatis Danubius. Œconomica, 2022)
Food price has continued to increase significantly and the oil price continues to be volatile in the midst of a downward trend in the external value of most currencies. This study purposes to shed light on the dynamic interaction between oil prices, exchange rates and food prices in BRICS and investigate the direction of the causality. The study also aims at determining the existence of an oil price threshold on the oil price and food price nexus. In order to achieve the objectives of the study, panel VAR and dynamic threshold models were employed using monthly data from January 2003 to March 2022. The findings show that oil prices and exchange rate shocks exert a significant influence on food prices. Our findings also show that oil prices and exchange rates are significant sources of variations in food prices. The findings confirm the existence of unidirectional causality from oil price to food price, and from exchange rate to food price. This study also establishes the existence of an oil price threshold on the nexus between oil price and food price. It can be recommended that the implementation of sound macroeconomic policies in the oil sectors keep the domestic oil price below the threshold level.